Welcome to Quantum Science and Technology. (12th August 2016) - Thew, Rob
Abstract: Quantum information science and related technologies now involve thousands of researchers worldwide, cutting across physics, chemistry, engineering, bioscience, applied mathematics and computer science, extending from fundamental science to novel applications and industry. This situation defines the scope and mission of Quantum Science and Technology, a new IOP journal  serving the interests of this multidisciplinary field by publishing research of the highest quality and impact.